GA3 and KCl Application as An Effort to Improve the Quality of Local Bali Grapes (Vitis vinifera L. var. Alphonso Lavallee) - Julfikar Julfikar; Ida Ayu Putri Darmawati; Rindang Dwiyani; Made Sri Sumarniasih; Anak Agung Sugiarta; Ni Luh Made Pradnyawathi; Yuyun Fitriani; I Made Basma Redana (Jurnal Penelitian Pendidikan IPA, 2025)
The global demand for table grapes continues to rise, driven by consumer preference for sweet, high-quality, and seedless fruit. Local varieties such as Bali grape (Vitis vinifera L. var. Alphonso Lavallee) remain less competitive than imported grapes due to small berry size, high acidity, and seed presence. This study evaluated the optimal concentrations of gibberellic acid (GA3) and potassium chloride (KCl) and their interaction effects on Bali grape fruit quality. The experiment used a factorial randomized complete block design with two factors: GA3 at 0, 50, 100, and 150 ppm, and KCl at 0 and 300 g per plant, with five replications. The results showed that GA3 significantly affected all observed parameters. Application of GA3 at 150 ppm produced the longest clusters, largest berry diameter, highest berry weight, and greatest sugar content, while simultaneously reducing seed number and seed weight, indicating induced parthenocarpy. KCl application significantly increased sugar content and berry diameter but did not influence seed characteristics. A significant interaction between GA3 150 ppm and KCl 300 g per plant was observed, resulting in the highest number of berries per cluster and the highest sugar concentration. Combined GA3 and KCl application improved fruit quality and enhanced Bali grape competitiveness